2020
DOI: 10.26434/chemrxiv.13102307.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Catalytic Asymmetric Reductive Alkylation of Enamines to Chiral Aliphatic Amines

Abstract: <p>Herein, we report a mild and general nickel-catalysed asymmetric reductive alkylation to effectively convert enamines—a class of important yet underexploited feedstock chemicals—into drug-like α-branched chiral amines and derivatives. This reaction involves the regio- and stereoselective hydrometallation of an enamine to generate a catalytic amount of enantioenriched alkylnickel intermediate, followed by C–C bond formation via alkyl electrophiles.</p>

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…alkyl halides are challenging to prepare, as functionalized alkenes are readily accessible than their functionalized alkyl halide counterparts. 35,36 Most recently, Hu's group, Shu's group, and our group independently demonstrated that the carbon stereocenter could be controlled using achiral enamides [37][38][39] and alkenyl boronates, 40 namely hydroalkylation of enamides or alkenyl boronates to produce enantioenriched aliphatic amines or alkyl boronates. In this context, we envisioned that this new strategy might realize the direct catalytic asymmetric synthesis of enantioenriched dialkyl carbinols and their derived esters (Scheme 1d).…”
Section: Obocmentioning
confidence: 99%
See 1 more Smart Citation
“…alkyl halides are challenging to prepare, as functionalized alkenes are readily accessible than their functionalized alkyl halide counterparts. 35,36 Most recently, Hu's group, Shu's group, and our group independently demonstrated that the carbon stereocenter could be controlled using achiral enamides [37][38][39] and alkenyl boronates, 40 namely hydroalkylation of enamides or alkenyl boronates to produce enantioenriched aliphatic amines or alkyl boronates. In this context, we envisioned that this new strategy might realize the direct catalytic asymmetric synthesis of enantioenriched dialkyl carbinols and their derived esters (Scheme 1d).…”
Section: Obocmentioning
confidence: 99%
“…Hu et al 40 Our group 37 ; Hu et al 38 ; Shu et al 39 hydroalkylation and hydroarylation of electronically unbiased alkenes in which unactivated alkenes were used as alkylmetallic equivalents. Concerning reductive hydroalkylation to access more valuable enantioenriched products, early examples focused on the coupling of functionalized halides with general alkenes.…”
Section: Obocmentioning
confidence: 99%
“…Moreover, the transition metal-catalyzed hydroalkynylation, hydroboration of internal enamide, and hydrofunctionalization of internal enamine derivatives recently were explored. Nevertheless, the highly regioselective hydroarylation of less reactive internal enamides by earth-abundant transition metal catalysis to access the benzylic amide derivatives has been seldom explored, which offers an alternative way to access benzylic amide compounds that can alternatively be prepared via hydroamination of styrenes (Scheme b) . Tremendous efforts have been devoted to accessing the various NiH-catalyzed hydrofunctionalizations of alkenes in the past few years. In this work, we disclose a Ni-catalyzed regioselective hydroarylation of internal enamides with aryl iodide and silane for intermolecular C­(sp 3 )–C­(sp 2 ) bond formation under mild conditions, while the regioselectivity arises from the chelation effect of the amide group.…”
mentioning
confidence: 90%
“…Herein, we reported the Ni-H catalyzed regio-and enantioselective reductive hydroalkylation of acyl enamines and enol esters with alkyl iodides to forge a stereogenic carbon center next to nitrogen or oxygen original from alkenes in high enantioselectivity, providing a uni ed protocol for rapid access to chiral dialkyl amine and alcohol derivatives which are di cult to access otherwise. [49][50][51] To test the feasibility of the reaction, we set out to identify the reaction parameters using acyl enamine 1a with 1-iodo-3-phenylpropane 2a as substrate in the presence of silane. (Table 1 and Tables S1-13).…”
mentioning
confidence: 99%